Specific Language Impairment and Language Delay: A Study on Enrollment in Language Schools in Chile - Granada-Azcárraga, Maribel (2023)
Introduction. Specific language impairment (SLI) and language delay (LD) are two different diagnostic categories presenting similarities at early ages. Objective. To determine trends and levels of significance of enrollment by gender over 14 years, using statistical information published by the Ministry of Education of Chile. Method. This research is a quantitative, exploratory study that analyzes the enrollment in language schools (n = 66) of boys and girls diagnosed with specific language impairment (SLI) in Maule, Chile. The study compares the enrollment trend with previous evidence described on the prevalence of both SLI and LD. Mann-Kendall’s tau test is used for the statistical analysis. In addition, a principal component analysis (PCA) is performed. Results. A significant trend (p < 0.05) is shown in the enrollment of children diagnosed with SLI in 22 schools analyzed. Fourteen are positive, and eight are negative. Enrollment of girls shows that significant trends are verified in 26 schools, where 23 are positive and 3 are negative over time. Discussion. Trends found in the enrollment of students diagnosed with SLI indicate that girls with RL are being incorporated into special language schools, and not only students with SLI. This finding would have implications for the identification, diagnosis, and educational support for students who present early difficulties in acquiring and progressing their language skills.